Development of an efficient method for oregano micropropagation - Rojas-García, Reyna; Ramírez-Godina, Francisca; Companioni-González, Barbarita; Vera-Reyes, Ileana; Robledo-Torres, Valentín; García-Osuna, Hermila Trinidad (Revista Mexicana de Ciencias Agrícolas, 2021)
Lippia graveolens, or Mexican oregano, is a plant of economic importance and the collection of foliage is mainly carried out from natural populations. Micropropagation proposes an alternative to produce material, with high phytosanitary quality and propagation in less time of individuals selected for their characteristics of commercial value. The objective of this work was to establish a protocol for the in vitro propagation of Lippia graveolens. The research was conducted in 2018-2019. The establishment was achieved with nodal segments in basal medium (MS), at this stage 57.32% of axenic explants were recovered. For the propagation stage four concentrations (0, 1, 2 and 3 mg L-1) of benzylaminopurine (6-BAP) were added to the MS medium, the number of shoots and height of the plan were evaluated, the best results in multiplication were achieved with 3 mg L-1 of 6-BAP, obtaining 40.35 shoots per explant. The length of the shoot was longer in treatments without growth regulators. For rooting, it was tested with three concentrations (0, 0.1, 0.3 and 0.5 mg L-1) of auxins (indole acetic acid and indole butyric acid) and the rooting percentage and root length were evaluated, obtaining the same result with and without auxin regulators. In the acclimatization phase, photoperiod (16 h and 24 h) was evaluated with and without mycorrhizas (Glomus intraradicens). The best treatment was obtained with 24 h light and the addition of mycorrhizas with 86.11% survival.
Keywords: Glomus intraradicens; biotización; fotoperiodo